Lamunkhinsky Evens: Population and Settlement in 20th - 21st Centuries - V. V. Filippova (Научный диалог, 2017)
The historical dynamics of the population and changes in settlement of one of the local groups of Yakutia Evens - lamunkhintsy - is considered. The author emphasizes that the territory of residence of this group of the Evens is one of the few areas of settlement of Yakutia Evens, where the traditional culture and native language is still preserved. It is reported that currently the boundary of the settlement of this ethnic group is limited by the administrative border of the municipality “Lamynkhinsky national nasleg” of Kobyaysky District of Sakha Republic (Yakutia). The novelty of the study is in determining the number of the Even population in the target group on the basis of previously unclaimed primary sources, census of the population of Yakutia and documents of the regional archives. Features of settlement of this group of the Evens are characterized according to the census of the population in 1926-1927 and 1939 due to the lack of information on the number of lamynkhinsky Evens for this period in Russian historiography. The causes of fluctuations in population and changes of the territory occupied by the local group of the Evens in the 20th - early 21st century are identified. The article presents the results of the project No. 17-11-14003 supported by the Russian Humanitarian Scientific Fund.